Characterization of Multiple Resistance Genes of Escherichia coli Strains Isolated from Food and Clinical Samples: Characterization of Multiple Resistant E. coli - Yelimlibağ, Birgül; Aydin, Muhsin (Cellular and Molecular Biology, 2023)
Multi-drug resistance (MDR), which is formed by the development of antimicrobial resistance, which is one of the defense mechanisms in bacteria, has pushed human beings to constantly seek new antimicrobial agents in the fight against these microorganisms. Speed and precision are very important in identifying resistance in strains with MDR that reach humans in an open system through the consumption of contaminated food or water. The main aim of this study was the molecular characterization of ESBL gene variants (blaTEM, blaOXA, blaSHV, and blaCTX-M), integron genes (int1, int2, and int3), and sulphonamide (sul1, sul2, and sul3) resistance genes by PCR from E. coli isolates originated from food and clinical samples. A total of 17 sets of primers were used for phylogenetic identification, molecular detection, and resistance and integron gene characterization of phenotypically identified E. coli isolates. The 45 red meat samples were collected from local markets, which are located in four (Adıyaman, Gaziantep, Kahramanmaraş, and Hatay) different provinces, clinical isolates were obtained from urine samples of patients with UTI from Şanlıurfa Mehmet Akif İnan Training and Research Hospital. Three gene groups were screened with 3 multiplex PCR applications in 63 food and 33 clinical isolates found to be E. coli by molecular identification. In terms of the 3 gene groups screened in food samples, the highest rates were found in the blaSHV gene at 44.44%, the sul1 gene at 69.84% and the int2 gene at 73.02%; in clinical samples, it is listed as blaCTX-M gene at 15.15%, sul2 gene at 81.82% and int1 gene at 54.55%. In terms of 3 gene groups scanned, the presence of 3 or more genes, including at least one gene from each gene group, was detected in 31 isolates from food samples and 2 isolates from clinical samples. Overall, it can be said that the high frequency of MDR genes isolated from E. coli-contaminated red meat samples and clinical samples gives a clue about the overuse of antibiotics in Türkiye.